Análise semi-clássica da interação do momento de quadrupolo magnético de uma partícula neutra com campos externos - Vieira, Samuel Lucas da Rocha (2019)
Based on the Maxwell duality, we consider non-uniform magnetic fields produced by non-uniform magnetic charge densities and non-uniform electric fields produced by uniform and non-uniform magnetic current densities. Then, we analyse the interaction of these fields with the magnetic quadrupole moment of a neutral particle from a semiclassical point of view, by applying the WKB (Wentzel, Kramers, Brillouin) approximation.